Persepsi Dosen dan Mahasiswa terhadap Penggunaan Teknologi dalam Kegiatan Belajar Mengajar di Universitas Al-Qolam Malang - Hosniyeh (Jurnal Tinta, 2025)
ABSTRACT  The focus of this research is what are the perceptions of lecturers and students regarding the use of technology in teaching and learning activities at Al-Qolam University Malang. This research uses descriptive qualitative methods. The data source in this research is the results of answers from a questionnaire distributed by researchers to representatives of 10 students and 10 lecturers from 10 study programs at Al-Qolam University Malang. Data collection used in this research was: Observation, interviews and documentation. The data analysis technique in this research consists of three paths, namely data reduction, data presentation, and drawing conclusions. The results of this research are that the majority of lecturers and students use technology in teaching and learning activities. They answered that the use of technology in learning is very effective and interesting, but apart from that, there are obstacles in using it such as facilities, not having internet access, not having a cellphone or laptop, not understanding the use of technology, etc. And one of the problems is that students become lazy about reading and studying, they prefer playing games and social media rather than reading and looking for material.